Breaking the 1, 2-HOPO barrier with a cyclen backbone for more efficient sensitization of Eu(iii) luminescence and unprecedented two-photon excitation properties. Issue 17 (4th April 2019) - Dai, Lixiong; Lo, Wai-Sum; Gu, Yanjuan; Xiong, Qingwu; Wong, Ka-Leung; Kwok, Wai-Ming; Wong, Wing-Tak; Law, Ga-Lai
Abstract : Breaking the barrier of 1, 2 HOPO complexes with extremely emissive Eu-Cy-HOPO (overall quantum yield −30.2%) that displays two photon properties. Abstract : A cyclen backbone was utilized to study the effect of backbone rigidity on Eu(iii ) luminescence sensitization using a 1, 2-HOPO derivative and 2-thenoyltrifluoroacetonate (TTA) as chromophores. The restriction of molecular movement of Eu-Cy-HOPO brought about by the increased rigidity provided a tightly packed coordination environment for the octadentate Eu(iii ) center which resulted in the highest overall quantum yield (30.2%) and sensitization efficiency (64.6%) among 1, 2-HOPO sensitized Eu(iii ) complexes. Eu-Cy-HOPO is also the first 1, 2-HOPO-based lanthanide complex to emit Eu(iii ) luminescence under two-photon excitation.